2015
DOI: 10.1186/s12885-015-1364-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of JWA, XRCC1 and BRCA1 mRNA expression on molecular staging for personalized therapy in patients with advanced esophageal squamous cell carcinoma

Abstract: BackgroundDNA damage repair genes JWA, XRCC1 and BRCA1 were associated with clinical outcomes and could convert the response to the cisplatin-based therapy in some carcinomas. The synergistic effects of JWA, XRCC1 and BRCA1 mRNA expression on personalized therapy remain unknown in advanced esophageal squamous cell carcinoma (ESCC).MethodsWe employed quantitative real-time polymerase chain reaction (qPCR) to determine the expression of JWA, XRCC1 and BRCA1 mRNA in paraffin-embedded specimen from 172 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Conversely, high BRCA1 expression was also positively associated with clinical outcomes in those who received docetaxel-fluorouracil chemotherapy. As a dual predictive biomarker, the results were consistent with previous findings by the present authors (40,41). The findings supported the hypothesis that the use of a combination of HDRA and qPCR is able to effectively distinguish biomarkers in their ability to evaluate response to chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, high BRCA1 expression was also positively associated with clinical outcomes in those who received docetaxel-fluorouracil chemotherapy. As a dual predictive biomarker, the results were consistent with previous findings by the present authors (40,41). The findings supported the hypothesis that the use of a combination of HDRA and qPCR is able to effectively distinguish biomarkers in their ability to evaluate response to chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…As a validation, all existing clinical prognostic parameters, including primary tumour size, lymph node involvement, as well as distant metastasis were strongly associated with patients’ overall survival (online supplementary figure 6 ), confirming that the combined cohort was valid for assessing prognostic biomarkers. We found that mutations of several driver genes (all SMGs except for BRCA1 , which was tested because it has been associated with treatment response and survival in oesophageal cancer 26–28 ) were associated with patients’ outcome in univariate log-rank analysis, including EP300, AJUBA and BRCA1 in OSCC, and FBXW7 and PTEN in OAC ( figure 3A , online supplementary figure 6 ). EP300 mutation and PTEN protein loss were observed to have significant detrimental effects on survival in independent OSCC and OAC cohorts, 8 29 respectively, supporting the present finding.…”
Section: Resultsmentioning
confidence: 99%
“…Also, we obtained 25 advanced or metastatic cases (stage III or IV) treated with first-line cisplatin-based regimen, and their median age was 61 (48-81 years) and 16 cases were male. Treatment outcome was evaluated according to the Response Evaluation Criteria Evaluation in Solid Tumors (RECIST) system [18]. All patients signed their informed consent.…”
Section: Patients Collectionmentioning
confidence: 99%